2015
DOI: 10.1007/jhep01(2015)058
|View full text |Cite
|
Sign up to set email alerts
|

Bending branes for DCFT in two dimensions

Abstract: We consider a holographic dual model for defect conformal field theories (DCFT) in which we include the backreaction of the defect on the dual geometry. In particular, we consider a dual gravity system in which a two-dimensional hypersurface with matter fields, the brane, is embedded into a three-dimensional asymptotically Anti-de Sitter spacetime. Motivated by recent proposals for holographic duals of boundary conformal field theories (BCFT), we assume the geometry of the brane to be determined by Israel junc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(119 citation statements)
references
References 102 publications
5
114
0
Order By: Relevance
“…Now we have shown that, holographic BCFTs with DBC and NBC have the same solutions, i.e., Poincare AdS (14) together with the embedding function of Q (15). As a result, they have the same boundary entropy and boundary central charges related to Euler densities and thus both obey g-theorem.…”
Section: Holographic Bcft With Dirichlet Bcmentioning
confidence: 78%
See 2 more Smart Citations
“…Now we have shown that, holographic BCFTs with DBC and NBC have the same solutions, i.e., Poincare AdS (14) together with the embedding function of Q (15). As a result, they have the same boundary entropy and boundary central charges related to Euler densities and thus both obey g-theorem.…”
Section: Holographic Bcft With Dirichlet Bcmentioning
confidence: 78%
“…So the holographic BCFT with Dirichlet BC is well-defined. As a quick check, we notice that the Poincare AdS (14) together with the embedding function of Q (15) are indeed solutions to the Dirichlet BC (63). As a result, holographic BCFT with Dirichlet BC share most of the advantages of holographic BCFT with Neumann BC [21].…”
Section: Holographic Bcft With Dirichlet Bcmentioning
confidence: 82%
See 1 more Smart Citation
“…Since in 2 + 1 dimensions gravity has no propagating degrees of freedom, the only effect is to impose some gluing condition between the geometry to the ‘left’ and to the ‘right’ of the defect. The conditions are the Israel junction conditions with the energy‐momentum tensor of the fields on the defect (see for a detailed analysis). This approach was applied to the holographic impurity model in , the result is summarized in Figure .…”
Section: Holographic Model Of the Kondo Effectmentioning
confidence: 99%
“…It might be interesting to explore such a possible connection further [95], as well as to reproduce Eq. (18) in the holographic models aspiring to describe the Kondo physics [103][104][105][106][107].…”
Section: Emergent Geometry and 'Holography Light'mentioning
confidence: 99%